Development of an Immunochromatographic Strip for Rapid Detection of Canine Adenovirus - Wang, Shujie; Wen, Yongjun; An, Tongqing; Duan, Guixin; Sun, MingXia; Ge, Jinying; Li, Xi; Yang, Kongbin; Cai, Xuehui (Frontiers in Microbiology, 2019)
Although canine adenovirus (CAdV) is highly prevalent in dogs, there is currently a lack of a quick diagnostic method. In this study, we developed a rapid immunochromatographic strip (ICS) assay using colloidal gold coupled to CAdV-2-specific monoclonal antibodies (mAbs). BALB/c mice were immunized with a purified CAdV-2 suspension, and four mAbs (belonging to two different epitopes) were generated and designated as 2C1, 7D7, 10D1, and 4G1. Western blot and protein spectral analysis indicated that the hexon protein of CAdV-2 recognized all four mAbs. The colloidal gold-coupled 7D7 and 2C1 mAbs were chosen for inclusion in the rapid ICS assay. The optimal concentrations of the coating antibody (2C1), the capture antibody (7D7), and the goat anti-mouse antibody were 1.0 mg/ml, 10 μg/ml, and 2.0 mg/ml, respectively. The limit of detection was approximately 2.0×102 tissue culture infective dose (TCID50)/ml. Other common canine viruses were tested to evaluate the specificity of the ICS, and positive results were observed for only CAdV-1 and CAdV-2. The ICS test was conducted on 360 samples to detect CAdV, and the results were compared with those of polymerase chain reaction (PCR) tests. The ICS test was found to be a sufficiently sensitive and specific detection method for the convenient and rapid detection of CAdV.